2013
DOI: 10.3111/13696998.2013.807813
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of lurasidone vs aripiprazole among patients with schizophrenia who have previously failed on an atypical antipsychotic: an indirect comparison of outcomes from clinical trial data

Abstract: Based on this model, when switching from another atypical antipsychotic, lurasidone had fewer relapses and hospitalizations with a lower incidence of diabetes and CV events than aripiprazole. Additionally, lurasidone may be less costly than aripiprazole among adults with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(42 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…Results of the base-case cost-effectiveness analyses showed that brexpiprazole was the dominant treatment strategy compared with lurasidone and cariprazine for all outcomes assessed. Although this is the only cost-effectiveness analysis of brexpiprazole compared to lurasidone and cariprazine we are aware of, the cost-effectiveness of lurasidone has been explored in previous studies; 36 – 38 however, these models included different populations, comparators, inputs, assumptions, and time horizons, making comparison across studies difficult. Model results should be considered in light of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the base-case cost-effectiveness analyses showed that brexpiprazole was the dominant treatment strategy compared with lurasidone and cariprazine for all outcomes assessed. Although this is the only cost-effectiveness analysis of brexpiprazole compared to lurasidone and cariprazine we are aware of, the cost-effectiveness of lurasidone has been explored in previous studies; 36 – 38 however, these models included different populations, comparators, inputs, assumptions, and time horizons, making comparison across studies difficult. Model results should be considered in light of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study comparing lurasidone with aripiprazole for second-line use in patients with schizophrenia found lurasidone to be cost-effective 36. This is the first cost-effectiveness analysis comparing lurasidone with other AAPs for firstline use in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 78%
“…The data on economic evaluation were extracted on a spreadsheet preformatted in Microsoft Excel® by two independent authors (ICBH and TML), and any disagreement was resolved by a third author (PMA). The following data were extracted type of economic evaluation, type of population, country, payer's perspectives, reference [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] which fully met the eligibility criteria were selected for this systematic review (Figure 1).…”
Section: Data Extractionmentioning
confidence: 99%
“…Most of the studies have not established an age group of the target population, and four studies have focused on adult patients. 14,[19][20][21] In addition, none of the studies have established the definition of the age groups (eg 30-50 years). Eight studies specified the phase at which the patients with schizophrenia entered the study (eg remission, acute phase, right after the failure of antipsychotic therapy, hospitalization), [14][15][16][17]21,[28][29][30] and only one study has specified the onset age of the disease.…”
Section: Characteristics Of the Full Economic Evaluationsmentioning
confidence: 99%